THE USE OF MICROSOFT TEAMS AS AN ONLINE PLATFORM IN ELT CLASSROOM DURING THE PANDEMIC: STUDENTS’ PERCEPTION - Zahra Elbanisa; Sueb Sueb (Universitas Muhammadiyah Tangerang, 2022)
During the COVID-19 pandemic, Indonesia is currently implementing a new policy that is teaching and learning activities from a distance, or we can call it learning from home or online learning. All education institutions require teachers and students to use online platforms to continue the learning process. The research aimed to find out the students’ perception of using Microsoft Teams as an online platform during the pandemic. This research was categorized as an explanatory-sequence approach. This study involved 8th-grade students (N=18) from the public junior high school in Surabaya. Eighteen items of questionnaires have been distributed. The findings revealed that the majority of the students involved in this study have a good perspective on using Microsoft Teams as an online platform; because of the ease of the use of Microsoft Teams, the students feel that the features of Microsoft Teams are pretty useful for them as the students, but even though most of them enjoy using Microsoft Teams, they prefer to choose to do classical learning which can be known as traditional learning.